CODE SWITCHING: A CASE STUDY OF GERMAN-RUSSIAN LANGUAGE INTERACTION - Serzhanova, Zhanna; Baykova, Olga; Kryukova, Natalya; Mishutinskaya, Elena (Revista Inclusiones, 2020)
Studying speech behavior of the linguistic identity carriers on the example of code switching seems quite relevant today. Despite extensive research on the subject of the relationship between language and culture and numerous scientific publications devoted to national and cultural characteristics of the linguistic identity, there have been no comprehensive studies on speech behavior of the Russian Mennonites. Another issue that remains insufficiently studied is also the factors that have an impact on the process of code switching and typological parameters of the linguistic identity.